Rational economics in comparison to the case of behavioral economics - Challoumis Constantinos; Savić Marko; Pavlović Nikola (Ekonomski Signali)
This paper aims to represent the special characteristics of rational economics in comparison to the case of behavioral economics. Therefore, this analysis represents these issues and shows the main differences between the two concepts. The mainstream is to show the crucial attributes of both of them and the differences between them. Behavioral economics also take into account subjective characteristics, while rational economics is based more on mathematical norms, but there are also approaches that allow both behavioral economics and behavioral economics as feedback systems can find the most appropriate model.